Community development as an embodiment of pastoral care in Africa: A public practical theology perspective - Nanthambwe, Patrick (Stellenbosch theological journal, 2022)
The pursuit of a fulfilling existence is a common goal among all human beings. As a result, promoting and sustaining quality humanhood or personhood (quality life) is the ultimate goal that international institutions, continental and regional bodies, and nations strive for. From a religious standpoint, theology and Christian religion need to contribute to helping people achieve the quality of life that humanhood aspires to. Consequently, pastoral care as a frontline ministry is positioned to play a leading role in fulfilling this function within church settings. Due to the public nature of this responsibility, the pastoral ministry should acquire a public pastoral care dimension in which community development is enhanced. Therefore, this article argues for public pastoral care as a solution to meeting the challenges faced by communities in Africa.